Pathways for the synthesis of glucosylglycerate, from Antarctica to deep sea hydrothermal vents : genes, enzymes and evolutionary implications - Costa, Joana Cardoso da (2008)
Tese de doutoramento em Biologia (Microbiologia) apresentada à Fac. de Ciências e Tecnologia de Coimbra